(untitled) (Fiep Bulletin - online, 2012)
The alterations in level of the feet as hallux valgus, amputations, fingers in hammers and pains are observed with large frequency in the elderly, due to factors related to their age or associated pathologies. The present work had as objective to evaluate the elderly individuals’ feet admitted to the University Hospital of West Paraná (HUOP) and to describe the found alterations. Were evaluated 180 patients of both sex, with medium age of 77.8 years old. A structured questionnaire was used that searched for information about the presence of pain in the feet, plane foot or concavous, hallux valgus, callosities, keratoses to plant, alterations in the fingernails and fingers hammers. The results showed that 40% of the individuals related pain in the feet, 50% presented hallux valgus, 50% plane foot, 72% fissures in the fingernails and 10% parestesies in the feet. It concludes that there is a high incidence of alterations in the elderly’s feet that composed the sample that can affect the quality of these individuals’ life negatively, what aims the need for preventive measures.